Pemberdayaan Masyarakat dalam Penerapan Modifikasi Quantum Ikhlas Sebagai Pencapain Dimensi Spritual Lansia Tangguh untuk Mengendalikan Kejadian Hipertensi di Wilayah Kerja Puskesmas Kota Utara Kota Gorontalo - Lusiane Adam; Ruliyani Manumba; Fatmawati Mohamad (Nanggroe: Jurnal Pengabdian Cendikia, 2023)
North City Public Health Center is a health service center located in the center of Gorontalo City with a high number of hypertension cases and is dominated by the elderly. Therefore, a community empowerment program is needed to support improving the health status of elderly people with hypertension in achieving resilient elderly people, especially in the spiritual dimension, which is through the application of Ikhlas quantum modification. This activity was carried out in two stages. The first stage begins with a pretest and blood pressure measurement, after which education is provided regarding therapy. After being given education, participants were given Quantum Ikhlas modification therapy, and ended with a posttest. In the second stage, monitoring and evaluation was carried out by measuring the elderly's blood pressure again after applying the Quantum Ikhlas modification therapy with istighfar. The Quantum Ikhlas modification used in this activity is audio istigfar which includes the words istigfar in it as well as a recording of the words tafakur. There was an increase in knowledge and a decrease in blood pressure in the elderly after being given education and Ikhlas Quantum Modification therapy with Istigfar. It is hoped that the Community Health Center can maintain the continuity of the implementation of Ikhlas Quantum Modification therapy with Istigfar by monitoring and evaluating regularly.